Penerimaan Pajak Daerah Kota Bandar Lampung Sebelum Dan Sesudah Penggunaan Tapping Box - Muhammad Raihan; Susi Sarumpaet; Dewi Sukmasari (LPPM ISNJ Bengkalis, 2021)
The research objectives were to examine the differences between the achievement of tax revenues in Bandar Lampung before and after using the tapping box; moreover, to analyze the implementation, obstacles, and efforts to overcome the obstacles during the use of the tapping box. This research uses mixed methods, namely quantitative and qualitative approaches. This study uses primary and secondary data. Primary data includes interviews with the regional tax and retribution management agency (RTRMA) and restaurant, hotel, entertainment, and parking businesses. Secondary data includes reports on the realization and target of restaurant taxes, hotel taxes, entertainment taxes, and parking taxes every month during the 2017-2019 period, totalling 24 data obtained from the RTRMA of Bandar Lampung. The hypothesis testing was using paired sample t-test. The results showed significant differences in the tax achievement of restaurants, hotels, entertainment, and parking between before and after using the tapping box sequentially. The implementation of the use of tapping box was going well, and it is proven that the tax achievement of restaurants, hotels, entertainment, and parking increases every month. So, the use of the tapping box already provided supervision to taxpayers. So, tax leaks can be minimized and increase the original local government revenue of Bandar Lampung.